Investigation of microstructure and mechanical properties of Cu/Ti–B–SiCp hybrid composites. Issue 21 (1st November 2021) - Şap, Serhat; Turgut, Aydın; Uzun, Mahir
Abstract: In this study, Cu/Ti–B-SiCp hybrid composite materials were produced by powder metallurgy method using three different sintering temperatures (950, 1000, 1050 °C). The optimum sintering temperature of Cu main matrix composites reinforced with Ti–B-SiCp reinforcement materials at 2-4-6-8 wt.% were determined and their microstructure and mechanical properties were investigated. As a result of microstructure studies, it was determined that reinforcement elements have a homogeneous interface in the main matrix. The hardness of the produced composites was determined by the Brinell hardness method. The highest hardness value (77.74 HB) was determined in the sample with 6 wt% reinforcement ratio. In the tensile and three point bending tests, maximum strength values (112.96 MPa, 37.76 MPa) were found in samples with a reinforcement ratio of 4 wt%. It was determined that increasing reinforcement ratios and sintering temperature made a positive contribution to the hybrid composite materials produced.